STUDENTS' PERCEPTIONS AND MOTIVATIONS OF URBAN AGRIPRENEURSHIP INTERESTS - Andika Kyo Putra; Syarif Imam Hidayat; Pawana Nur Indah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to: Analyze students' perceptions and motivations towards urban Agripreneurship interests. The population in the study is active students of the Agribusiness Study Program, Faculty of Agriculture, UPN "Veteran" Jawa Timur. The sample was selected using a multistage random sampling method with a total of 100 respondents including students in semester 6 and 8. This research uses the SEM-PLS method with the help of Smart-PLS software. The results of this study show: Students have a positive perception, high motivation, and high interest in urban Agripreneurship in the city of Surabaya. This shows that there is great potential for the development and strengthening of urban agripreneurship in the academic environment and the wider community. Conclusion of this study: This study identifies urban Agripreneurship as a phenomenon of interest in Surabaya City. Urban agripreneurship includes agricultural and business activities conducted in urban environments, focusing on technological innovation and environmental sustainability; The results of the analysis show that students in Surabaya have a positive perception of urban agripreneurship. They see the profit potential and its positive impact on the environment as factors driving their interest. Student motivation is also high, especially in following the latest technological developments in agriculture